2011
DOI: 10.1038/leu.2011.95
|View full text |Cite
|
Sign up to set email alerts
|

The role of Smad signaling in hematopoiesis and translational hematology

Abstract: Hematopoietic stem cells (HSCs) reside in the bone marrow (BM) of adult individuals and function to produce and regenerate the entire blood and immune system over the course of an individual's lifetime. Historically, HSCs are among the most thoroughly characterized tissue-specific stem cells. Despite this, the regulation of fate options, such as self-renewal and differentiation, has remained elusive, partly because of the expansive plethora of factors and signaling cues that govern HSC behavior in vivo. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 131 publications
2
78
0
Order By: Relevance
“…In this paper, we elucidated a novel function of TGF-b, a well-known negative regulator of cell proliferation, 7,8,[12][13][14] in the retention of HSPCs within the BM niche. Although it is well established that the localization of HSPCs in the niche is essential for lifelong maintenance of hematopoiesis, [1][2][3] how and why HSPCs stay in the niche have been rarely discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we elucidated a novel function of TGF-b, a well-known negative regulator of cell proliferation, 7,8,[12][13][14] in the retention of HSPCs within the BM niche. Although it is well established that the localization of HSPCs in the niche is essential for lifelong maintenance of hematopoiesis, [1][2][3] how and why HSPCs stay in the niche have been rarely discussed.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] HSPCs in close proximity to megakaryocytes exhibit Smad2/ 3 activation, and conditional deletion of TGF-b from megakaryocytes results in reduced phosphorylation of Smad2/3 as well as loss of quiescence and increased HSPC proliferation. Although TGF-b has been characterized as a negative regulator of HSPC proliferation, [12][13][14] its role in HSPC motility has not been studied. Meanwhile, it has been reported that plasminogen activator inhibitor (PAI)-1, a well-known downstream molecule of TGF-b signaling 15,16 and a major physiologic inhibitor of the fibrolytic system that inhibits the serine protease activity of urokinase and tissue plasminogen activator (tPA) during blood clotting, 16 regulates adhesion and migration of many cell types, including hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes containing activin receptor type IIA (ActRIIA), ActRIIB, or the TGFb type II receptor regulate gene expression primarily by activating the Smad2/3 subfamily of intracellular effectors, whereas BMP receptors and ligands signal primarily through Smad1/5/8. 12 Studies have documented effects of several superfamily ligands on erythroid precursors or cell lines, but the role of this superfamily in regulating erythropoiesis in vivo is not well understood. [12][13][14][15] Intriguingly, increased Smad2/3 activation is found in hematopoietic progenitors from patients with myelodysplastic syndromes (MDS), 16 a heterogeneous group of blood disorders in which IE occurs due to abortive erythroid precursor maturation.…”
Section: Introductionmentioning
confidence: 99%
“…13 SKI does not bind to DNA directly, 14 but when associated with active Smad-complexes it blocks their ability to initiate gene expression. [15][16][17][18][19][20][21] We have recently demonstrated that the Smad-signaling circuitry is intimately linked to HSC regulation, [22][23][24][25] suggesting that SKI may play a role in controlling hematopoiesis. To generate a model for investigation of the intrinsic role of SKI in hematopoiesis and its potential role in myeloid neoplasms, we have over-expressed human SKI in adult murine hematopoietic stem and progenitor cells.…”
Section: Introductionmentioning
confidence: 99%